PENGARUH BUDAYA ORGANISASI TERHADAP EMPLOYEE ENGAGEMENT DAN LOYALITAS PEGAWAI PADA GENERASI MILENIAL - Ahmad Syaihu (MediaKom : Jurnal Ilmiah Komunikasi, 2019)
Millennial generation is a generation born in the era of the 80-90s, so that at this time the millennial generation is the most dominant generation in a company. Organizational culture in a company must follow developments in accordance with the current millennial generation. Employee engagement and employee loyalty are very important factors in achieving the goals of a company. PT Bank Mandiri is one company that has employees mostly in the millennial generation. Therefore, the organizational culture that exists at PT Bank Mandiri must adjust to the current generation. The TIPCE culture is still held tightly by PT Bank Mandiri as the main foundation of organizational culture. Along with the times, the work culture at PT Bank Mandiri also adjusts the existing work culture with the current millennial generation. This research was conducted to determine how much influence the work culture has on employee engagement and employee loyalty, especially in the millennial generation at PT Bank Mandiri, Cash & Trade Operations Group. By using quantitative methods and surveys conducted and using Co-Operation theory from Taylor and colleagues according to Taylor, organization is a circular process, with interactions and interpretations that influence each other. In other words, interaction results in shared meaning which then shapes our interactions.